Peran Diplomasi Ekonomi Berkelanjutan dalam Mewujudkan Indonesia Emas 2045 - Muhammad Farhan Surez (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article examines the strategic role of sustainable economic diplomacy in achieving the vision of Golden Indonesia 2045. Sustainable economic diplomacy is defined as diplomatic efforts aimed at promoting environmentally friendly and inclusive economic growth through strong international relations, trade agreements, economic cooperation, and foreign direct investment (FDI). The analysis shows that through economic diplomacy, Indonesia can gain access to international markets, attract FDI, foster innovation and technology transfer, and strengthen regional and multilateral cooperation. These strategies support inclusive and environmentally sustainable economic growth, helping Indonesia to overcome global challenges and achieve long-term development goals. Recommendations include strengthening the capacity of economic diplomacy, effective inter-agency coordination, and inclusive policies.